Ідея cправедливості у праві: історичний аспект - Гусарєва, О.С. (Альманах права, 2012)
У статті характеризується правова природа та генезис ідеї справедливості як фундаментальної правовоїцінності. Висвітлюються особливості ідеї справедливості у праві на різних історичних етапах її розвитку, розкривається її значення для сучасної правової теорії та практики як фундаментального принципу права. В статье характеризуется правовая природа и генезис идеи справедливости как фундаментальной правовой ценности. Раскрываются особенности идеи справедливости в праве на разных исторических этапах ее развития, а также ее значение для современной правовой теории и практики как фундаментального принципа права. This article is characterized by the legal nature and genesis of the idea of justice as a fundamental legal value. The peculiarities of law is the idea of justice in different historical stages of its development and its relevance to modern legal theory and practice as a fundamental principle of law.Justice as a principle of law is one of the requirements of the correct application of the law and other forms of justice highlighted in the writings of many theorists of our time. At the same time, the problem of justice in the law are not covered in terms of mechanisms for its implementation and proper perception of society as fundamental values, ideals, which are aimed at achieving the various levers of social control. For the philosophy of ancient East and ancient Greece was inherent understanding of justice as a principle of the existence of internal nature, as physical, cosmic order, which appears in the social order. Occurrence of medieval philosophy preceded series of changes not only in economic and political relations, especially in ideology one orientation of the then society. Christianity became the dominant ideology in Europe and sought to find a philosophical justification of its basic ideas. A long time had the common philosophical position according to which true justice does not exist anywhere, except to the republic, the founder and ruler of which is Christ. During the Renaissance and Reformation man was the supreme value and ontological reality. The ideas of liberalism, parliamentarism, constitutionalism, human rights were a continuation of the right ideas of justice. During the 16-18 centuries, was singled out moral and legal justice, while it was also defined primacy of legal justice to the moral. Later, in search of justice as an abstract phenomenon was a focus on social, economic, political and legal justice. Most scholars agree that legal justice is a prerequisite for the realization of any truly moral act. So the idea of justice people as moral and legal category, the concept of credit, have changed throughout history, depending on the changes taking place in the consciousness of society regarding understanding of inalienable human rights (the influence of philosophy natural space living, Christian doctrine, ideas of anthropocentrism, etc. ). Modern Theory considers justice as a form of state activity as a basic constitutional principle of all government agencies and officials. Philosophy of Law by axiological approach considers justice as the highest value, protect and cultivate what is called the whole system of law. In a philosophical context, justice is seen as the concept of credit, which is determined in accordance with ideas about the nature of man and his inalienable rights. Reflected these provisions are in practical and legal activities with particular emphasis on the necessity to recognize the priority of justice in the legal profession, and the latter are considered as representatives of justice. Thus, justice acts as a moral and legal category, which recognizes ethics as a specifically moral, and lawyers — both specifically legal. Thus, we can consider justice not only as a world wide basis for modern comprehension, but also as a social phenomenon, which manifests itself in a peculiar manner the right of where it is appropriate to its selection as the basis of law, the principle requirements for regulation and so on.